2009
DOI: 10.1177/0363546509333479
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Isolated Anterolateral Bundle Reconstructions of the Posterior Cruciate Ligament

Abstract: Arthroscopically assisted reconstructions of the anterolateral bundle of the PCL in patients with symptomatic isolated grade II to IV PCL-deficient knees lead to significantly improved functional results at long term if there is no cartilage damage at time of surgery. Nonoperative treatment should not be extended more than 1 year from injury. Graft choice did not significantly influence the functional outcome at long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 51 publications
(78 reference statements)
8
78
1
1
Order By: Relevance
“…Isolated PCL tears are less common injuries and it would be difficult to gather enough patients for a comparative study. Second, a historical comparison of our data with those available in the literature is challenging, because numerous surgical variables such as graft tensioning and material, tunnel placement, screw parameters (diameter, length, material), or the position of the screw within the tunnel as well as clinical variables including associated injury at the time of injury or time between injury and surgery [9] could influence the outcome of the procedure. Nonetheless, our observations in these 10 PCLreconstructed patients after a combined distal and proximal fixation technique compared favorably with the observations by others ( Table 2) with no differences in activity level between the preoperative level and postoperatively and no difference in ROM between the PCL-reconstructed and contralateral normal knees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated PCL tears are less common injuries and it would be difficult to gather enough patients for a comparative study. Second, a historical comparison of our data with those available in the literature is challenging, because numerous surgical variables such as graft tensioning and material, tunnel placement, screw parameters (diameter, length, material), or the position of the screw within the tunnel as well as clinical variables including associated injury at the time of injury or time between injury and surgery [9] could influence the outcome of the procedure. Nonetheless, our observations in these 10 PCLreconstructed patients after a combined distal and proximal fixation technique compared favorably with the observations by others ( Table 2) with no differences in activity level between the preoperative level and postoperatively and no difference in ROM between the PCL-reconstructed and contralateral normal knees.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show nonoperative treatment will restore the functional activity level in some individuals with an isolated PCL injury [5,13,26,27]. Other studies suggest patients with more severe (Grade II or III) posterior laxity may experience chronic instability and associated pain [3,13,32] and have worse functional scores and increased articular degeneration on radiographic assessment as the time from injury increases [9,13]. Therefore, it is important to identify in a timely manner those patients in whom the injury is likely to result in persistent instability, knee pain, and degenerative arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…At a mean of 17 years after nonoperative treatment, Shelbourne et al [28] found that patients had a mean IKDC score of 73 points, which compares to IKDC scores of 75 and 87 found by studies of operative treatment that had much less follow-up times of 9-10 years [45].…”
Section: Treatment Outcomes: Nonoperative Versus Pcl Reconstructionmentioning
confidence: 87%
“…With a mean of 9 years after PCL reconstruction, Hermans et al [45] found medial joint line narrowing in 59 % of their patients and the IKDC ratings of radiographs were normal for 9 of 22 patients (41 %), nearly normal for 10 (45 %), and abnormal for 3 (9 %). Jackson et al [34] found evidence of OA in 8 of 22 patients at 10 years after PCL reconstruction; 4 patients had osteophytes but normal joint space width, and 4 (18 %) had moderate degenerative changes.…”
Section: Treatment Outcomes: Nonoperative Versus Pcl Reconstructionmentioning
confidence: 94%
“…As lesões do LCP, com maior instabilidade, geralmente se associam a déficit funcional, dor crônica e degeneração condral, evidenciada nos exames radiográficos (BOYNTON;TIETJENS, 1996;DANDY;PUSEY, 1982;HERMANS;CORTEN;BELLEMANS, 2009;KELLER et al, 1993;PAROLIE;BERGFELD, 1986;PATEL et al, 2007;DAVIS;PATEL, 1999). A evidência, portanto, indica que o tratamento cirúrgico deve ser considerado em casos selecionados em que seja identificada instabilidade moderada, incapacidade funcional e limitação das atividades da vida cotidiana.…”
Section: Tratamento Cirúrgicounclassified